1935
DOI: 10.1002/path.1700400204
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative estimation of the fragility of the red corpuscles

Abstract: Pathologist to The Bland-Sutton Institute, The Middlesex Hospital ; and M. HYNES, B.A., Demonstrator in Pathology, The Bland-Sutton Institute, The Middlesex Hospital.THE decreased resistance of the red corpuscles to relatively high concentrations of saline has long been known as an almost pathognomonic test for htemolytic icterus, whilst the wide application of the fragility test has shown that more information is given by a quantitative determination than by a simple qualitative test. But, except for Simmel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

1941
1941
1970
1970

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 3 publications
1
14
1
Order By: Relevance
“…The increase in osmotic resistance generally observed in red cells from cord blood in this study is in contradiction with the increased fragility reported by several authors [8,13]. The data obtained by the 50% hemolysis test are of limited value as can be seen from the considerable amount of overlap in the osmotic resistance values for cord and adult blood at this level of hemolysis ( fig.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…The increase in osmotic resistance generally observed in red cells from cord blood in this study is in contradiction with the increased fragility reported by several authors [8,13]. The data obtained by the 50% hemolysis test are of limited value as can be seen from the considerable amount of overlap in the osmotic resistance values for cord and adult blood at this level of hemolysis ( fig.…”
Section: Resultscontrasting
confidence: 56%
“…Goldbloom and Gotlieb [8] reported increased osmotic fragility of newborn red blood cells. Whitby and Hynes [13], cited by Wintrobe [14], claimed that the red blood corpuscles of newborn children are somewhat more fragile than those of adults, but did not regard the difference as significant. Waugh et al [12] reviewed 15 papers on the subject and concluded that fetal cells are slightly more resistant.…”
mentioning
confidence: 99%
“…An additional tube containing 1.0 per cent NaCl was included in the fragility test to mimic the additional osmotic effect of the serum protein, and no additional hemiolysis above that found in the serum itself was observed at this concentration of NaCl. Since estimation of per cent hemolysis on the basis of plasma hemoglobin measurements may introduce an error related to the amount of hemoglobin retained by individual hemolyzed or ghost cells, a more specific visual estimate of the percentage of hemolyzed cells was carried out in a manner somewhat similar to the original osmotic fragility studies of Whitby and Hynes (19), who used red blood cell counts. Stained cell preparations were made by placing 50 1l of the experimental cell suspensions into 10 ml of the 0.70 per cent NaCl-PO buffer (pH 7.4) described by and allowing the injured cells to hemolyze during 20 minutes of incubation at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The difference in the values of a in the two groups is also highly significant statistically: moreover, there is no overlap between the two. This index effectively 20 …”
Section: Resultsmentioning
confidence: 99%